Application of Restorative Justice Against Crime Committed by Children in Polres Cirebon - Iwa Mashadi; Gunarto Gunarto (Jurnal Daulat Hukum, 2018)
Kids are an integral part of the survival expressly stated that the state guarantees the right of every child to survival, grow, and develop as well as protection from violence and discrimination. The protection of children is not only given to children who are victims of crime, but also to children who become perpetrators of criminal acts, so that the legal process especially in providing criminal decisions should also consider the future of the child as it is for a country, children are the hope of the future country. Towards children who commit criminal acts is also subject to criminal sanctions. Talking about the criminalization of children often contentious, because this issue has very broad consequences related to both self and community behavior. Punishment is an element of criminal law, in which the criminal prosecution has negative consequences for the given criminal sanctions. Along with Act No. 11 of 2012. While the effectiveness of sanctions against children in the perspective of restorative jusitce in Polres Cirebon Jurisdiction is quite effective because the victim, the offender and the community are satisfied with the settlement of Restorative justice and remembering the birth of Act No. 11 of 2012 Kids on the Criminal Justice System.Keywords: Restorative justice, Crime Child.